#MeToo Social Media Engagement and Perceived Hypersensitivity in the Workplace. Issue 4 (4th July 2021) - Smith, Andrea M.; Ortiz, Rebecca R.
ABSTRACT: The #MeToo movement initiated a prominent shift in our awareness of sexual violence in the workplace by encouraging millions of survivors to share their experiences on social media and the movement sought to hold perpetrators accountable for their actions. This study examined how employees' selective engagement with the #MeToo movement influenced their acceptance of rape myths and their perceptions of the movement's impact on gender dynamics in the workplace (i.e., perceived increased hypersensitivity). A sample of U.S. employees completed the relevant measures in an online survey. Results indicated that the more a participant engaged with the #MeToo movement on social media the less accepting they were of rape myths and the less they perceived the #MeToo movement as increasing hypersensitivity about sexual assault and sexual harassment in the workplace. Practical implications for improving workplace dynamics, such as using employees' perceptions of the #MeToo movement to help inform organizational trainings, policies, and procedures are discussed.